Metal Micro-forming - Manabe, Ken-ichi (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The miniaturization of industrial products is a global trend. Metal forming technology is not only suitable for mass production and excellent in productivity and cost reduction, but it is also a key processing method that is essential for products that utilize advantage of the mechanical and functional properties of metals. However, it is not easy to realize the processing even if the conventional metal forming technology is directly scaled down. This is because the characteristics of materials, processing methods, die and tools, etc., vary greatly with miniaturization. In metal micro forming technology, the size effect of major issues for micro forming have also been clarified academically. New processing methods for metal micro forming have also been developed by introducing new special processing techniques, and it is a new wave of innovation toward high precision, high degree of processing, and high flexibility. To date, several special issues and books have been published on micro-forming technology. This book contains 11 of the latest research results on metal micro forming technology. The editor believes that it will be very useful for understanding the state-of-the-art of metal micro forming technology and for understanding future trends.